Intrathecal trastuzumab: immunotherapy improves the prognosis of leptomeningeal metastases in HER-2+ breast cancer patient - Nu T. Lu; Jeffrey Raizer; Erwin P. Gabor; Natalie M. Liu; James Q. Vu; Dennis J. Slamon; John L. Barstis (Journal for ImmunoTherapy of Cancer)
We describe the clinical and therapeutic course of a 51-year-old woman with HER-2+ breast cancer who developed leptomeningeal (LM) and spinal cord metastases after 8 years of stable disease on combination therapy with intravenous (IV) trastuzumab. Due to progressive CNS disease, intrathecal (IT) trastuzumab was introduced to enhance HER-2+ therapy into the CSF space. A combination HER-2+ targeted approach achieved clinical remission with stable disease in our patient 46 months after she was diagnosed with LM metastases. However, spinal cord C-1 metastasis was not fully controlled with IT trastuzumab, ultimately leading to the patient’s respiratory compromise. In our patient, IT trastuzumab immunotherapy improved prognosis and was an effective strategy to manage HER-2+ LM disease. Given alone or alongside other anti-HER-2+ therapeutics with sufficient CNS penetration, IT trastuzumab could extend the lifespan of patients with leptomeningeal and CNS metastases.